Eligibility for hematopoietic stem cell transplantation in a cohort of children with sickle cell disease: a single-center report - Khaled Salama; Asmaa F. Allam; Yasmeen M. M. Selim (SpringerOpen, 2024)
Abstract Background Hematopoietic stem cell transplantation (HSCT), is the only currently available curative option for SCD. Yet, the eligibility of SCD patients for HSCT is always limited by the significant associated toxicity and lack of suitable donors. At Cairo University's pediatric hematology outpatient clinic, we aimed to determine hematopoietic stem cell transplantation (HSCT) candidates among a sickle cell disease (SCD) cohort, estimate the number of possible donors, and analyze the differences between patients with and without an HSCT indication. Methods This study was a cross-sectional analytic study including 128 SCD children. Their demographic, clinical, and laboratory profiles, total number, and number of siblings with SCD were obtained from their medical records. Results Sixty-nine (53.9%) had at least one HSCT indication. Recurrent severe pain episodes despite hydroxyurea were the most common indication. Hemoglobin was lower, while reticulocyte count, serum ferritin, and aspartate aminotransferase were higher in HSCT candidates (p value < 0.001). Additionally, the prevalence of splenomegaly, the dose of hydroxyurea, and the number of transfusions were noticeably higher in HSCT candidates (p value = 0.013, 0.005, and < 0.0001 respectively). Among those indicated for HSCT; 75.3% had at least one healthy sibling who might be a potential donor. Conclusion More than half were eligible for HSCT which should always be considered to provide a possible cure for the disease. Of the transplantation-eligible cases, about two-thirds had at least one healthy sibling who might potentially serve as a donor. Those meeting the requirements for HSCT eligibility should routinely undergo human leukocyte antigen (HLA) testing of their unaffected siblings.